2019
DOI: 10.15252/embj.201899363
|View full text |Cite
|
Sign up to set email alerts
|

A multifaceted small RNA modulates gene expression upon glucose limitation in Staphylococcus aureus

Abstract: Pathogenic bacteria must rapidly adapt to ever‐changing environmental signals resulting in metabolism remodeling. The carbon catabolite repression, mediated by the catabolite control protein A (CcpA), is used to express genes involved in utilization and metabolism of the preferred carbon source. Here, we have identified RsaI as a CcpA‐repressed small non‐coding RNA that is inhibited by high glucose concentrations. When glucose is consumed, RsaI represses translation initiation of mRNAs encoding a permease of g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
92
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 50 publications
(93 citation statements)
references
References 70 publications
0
92
0
Order By: Relevance
“…Second, others have shown that rsaD is dependent on Sigma B (Geissmann et al, 2009), the alternative sigma factor responsible for activating the general stress response in S. aureus, as well as playing critical roles in virulence and persistence (Chaturongakul, Raengpradub, Wiedmann, & Boor, 2008;Hecker, Pané-Farré, & Völker, 2007;Mitchell et al, 2013;Novick, 2003;Tuchscherr et al, 2015). How SigB controls rsaD expression, whether by directly binding to the rsaD promoter or through an indirect method, requires further study since there exists a lack of understanding SigB activation in S. aureus compared to related (Bronesky et al, 2019). SrrAB is a regulatory system that influences virulence factor expression, including genes important for biofilm formation and even programmed cell lysis.…”
Section: Rsad Integrates Multiple Signals Into Staphylococcal Regulmentioning
confidence: 99%
“…Second, others have shown that rsaD is dependent on Sigma B (Geissmann et al, 2009), the alternative sigma factor responsible for activating the general stress response in S. aureus, as well as playing critical roles in virulence and persistence (Chaturongakul, Raengpradub, Wiedmann, & Boor, 2008;Hecker, Pané-Farré, & Völker, 2007;Mitchell et al, 2013;Novick, 2003;Tuchscherr et al, 2015). How SigB controls rsaD expression, whether by directly binding to the rsaD promoter or through an indirect method, requires further study since there exists a lack of understanding SigB activation in S. aureus compared to related (Bronesky et al, 2019). SrrAB is a regulatory system that influences virulence factor expression, including genes important for biofilm formation and even programmed cell lysis.…”
Section: Rsad Integrates Multiple Signals Into Staphylococcal Regulmentioning
confidence: 99%
“…It increases the translation of Sbi immune evasion molecules, and consequently weakens the innate and adaptive immune responses (22,23). In addition to these examples, only a handful of sRNAs have been assessed for functions, including identifying their targets (6,7,(24)(25)(26)(27)(28)(29)(30).…”
mentioning
confidence: 99%
“…In contrast, RosA is a stand-alone sRNA. Interestingly, another stand-alone sRNA in S. aureus , namely RsaI (RsaOG), was also shown to be CcpA-regulated and to interact with the sRNAs RsaG, RsaD and RsaE, the RoxS homologue in S. aureus , 52 . RsaI, like RosA, contains two G-rich regions to bind to RsaG, RsaD and RsaE.…”
Section: Discussionmentioning
confidence: 99%